The Role of the P2X(7) Receptor in Infectious Diseases - Miller, Catherine M. (Public Library of Science, 2011)
ATP is an extracellular signal for the immune system, particularly during an inflammatory response. It is sensed by the P2X(7) receptor, the expression of which is upregulated by pro-inflammatory cytokines. Activation of the P2X(7) receptor opens a cation-specific channel that alters the ionic environment of the cell, activating several pathways, including (i) the inflammasome, leading to production of IL-1β and IL-18; (ii) the stress-activated protein kinase pathway, resulting in apoptosis; (iii) the mitogen-activated protein kinase pathway, leading to generation of reactive oxygen and nitrogen intermediates; and (iv) phospholipase D, stimulating phagosome-lysosome fusion. The P2X(7) receptor can initiate host mechanisms to remove pathogens, most particularly those that parasitise macrophages. At the same time, the P2X(7) receptor may be subverted by pathogens to modulate host responses. Moreover, recent genetic studies have demonstrated significant associations between susceptibility or resistance to parasites and bacteria, and loss-of-function or gain-of-function polymorphisms in the P2X(7) receptor, underscoring its importance in infectious disease.